Probing the use of spectroscopy to determine the meteoritic analogues of meteors - Drouard, A; Vernazza, P; Loehle, S; Gattacceca, J; Vaubaillon, J; Zanda, B; Birlan, M; Bouley, S; Colas, F; Eberhart, M; Hermann, T; Jorda, L; et al. (EDP Sciences, 2018)
Context: Determining the source regions of meteorites is one of the major goals of current research in planetary science. Whereas asteroid observations are currently unable to pinpoint the source regions of most meteorite classes, observations of meteors with camera networks and the subsequent recovery of the meteorite may help make progress on this question. The main caveat of such an approach, however, is that the recovery rate of meteorite falls is low (<20%), implying that the meteoritic analogues of at least 80% of the observed falls remain unknown.